Penatalaksanaan stomatitis aftosa rekuren mayor dengan infeksi sekunder Management of major recurrent aphtous stomatitis accompanied by secondary infection - Nurdiana Nurdiana; M. Jusri (Journal of Dentomaxillofacial Science, 2011)
Recurrent aphthous stomatitis (RAS)is an ulcerative condition that affects the oral mucosa without evidence ofunderlying disorder. It’s characterized by the appearance of recurring round, shallow ulcerations surrounded byinflammation that mainly involves the nonkeratinized mucosa. The classification of SAR are minor, major, andherpetiform types. Although rare, secondary infection may occur. Treatment is directed to avoid local traumaticprecipitants, lessen the pain and duration of ulceration by suppressing the local immune response, and preventsecondary infection. The objective of this paper is to discuss the treatment of RAS with secondary infection, a caseof 24-year-old man with multiple large ulcers that did not heal for almost 4 weeks. The ulcers were diagnosed asmajor RAS with secondary infection, and treated with metronidazole and ciprofloxacin, healed in 2 weeks withscars. Although secondary infection will delay healing, but with proper treatment, major RAS has good prognosis.